Entrepreneurial Female Leadership: A Business Policy Approach to B Corp Management in Latin America - Ángel Acevedo-Duque; Rina Alvarez-Becerra; Sandra Alcina De Fortoul; Orietta Barriga-Soto; Giovanna Cúneo-Álvarez; Mirtha Mercedes Fernández-Mantilla; Carla Valdez-Alvarez (Administrative Sciences)
This study aims to analyze how women’s empowerment in sustainable entrepreneurial leadership transforms social, environmental, and economic challenges into growth opportunities within B Corps-certified companies in Latin America. A total of 9536 companies were identified in the global B Corps registry, of which more than 1000 belonged to the Latin America and Caribbean directory. Particular attention was given to 130 companies located in Chile, with a presence in countries such as Peru, Mexico, Colombia, Brazil, Uruguay, Paraguay, and Argentina. The methodology adopted a post-positivist approach with a hermeneutic analysis rooted in organizational studies, using the Straussian grounded theory method. Testimonies from 16 female entrepreneurs were explored, identified through the B Corps directory and the main social media networks of the B system in Latin America. This approach enabled a deeper understanding of the human complexity surrounding sustainability, equity, and gender equality. Findings show that female leadership promotes inclusive and strategic actions that challenge traditional structures and generate positive impacts. Five categories emerged: female entrepreneurial leadership; gender equality stakeholders; social contribution; women’s economic development; and sustainable decision-making. These converge in the central category of female empowerment in sustainable entrepreneurial leadership. In conclusion, the emerging theory expands the understanding of women-led leadership in Latin America, revealing socially responsible business models that promote sustainability, inclusion, and challenge dominant power structures in the business world.